The Renovation of She-Tragedy in Heather Raffo’s Nine Parts of Desire - Ali, Basma Abdulhasan (Al-Adab Journal, 2021)
During the 1990’s and the years of siege that followed, Iraqi women suffered from the oppression of the brutal misogynist regimes, and the cruel male-controlled ideals. Accordingly, through their suffering, these women portrayed the truth of being woman in a horrific atmosphere of war and how these traumatised women managed to survive. In her Nine parts of Desire, Heather Raffo presents the characters of nine different women of different ages and professions linking them to show the dreadful reality of being woman in the times of war. In this play, Raffo renovated the She-tragedy genre. Even though that this genre deals with weak frustrated women who suffer from the effect of the long lack of stability, years of internal violence, external occupation and their cumulative generational effects, yet Raffo’s characters are strong, confident and have a self-awareness and they stand face to face to the shocking values of war.